Pemberdayaan dan Simulasi Pembuatan Jus Bayam Merah dan Kurma Sebagai Upaya Penanggulangan Anemia Pada Siswi SMK NU 04 Ma’arif Pakis - Angernani Trias Wulandari; Nur Aini Al Hasana; Aligonda Songbes; Elisabetr Lonek Kewa Mahon (I-Com: Indonesian Community Journal, 2024)
Adolescent girls are more prone to anemia than boys. This happens because adolescent girls require more iron (Fe) as they lose iron during menstruation. Fatigue, weakness, dizziness, pallor, shortness of breath, impaired concentration, and decreased physical performance are common symptoms of anemia in adolescents. As future mothers of the nation, it is important to pay attention to the health of adolescent girls, including iron deficiency anemia. Prevention of anemia at a young age is beneficial for adolescent health and their cognitive abilities, as well as for the next generation, one of which is the prevention of stunting. The purpose of this service is to conduct health education about anemia, empowerment and simulation of making red spinach juice and dates in an effort to prevent and overcome anemia in adolescent girls at SMK NU 4 MAARIF PAKIS. The method in this service activity is to provide health education about anemia and simulation of making red spinach juice and dates. The result of this service is an increase in knowledge about anemia obtained from the pre-test results of 6.58 and post-test results of 9.34. Based on the above results, it can be concluded that the aim of increasing knowledge about anemia with health education is achieved and empowerment for anemia prevention by making red spinach juice and dates is achieved.